2014
DOI: 10.1016/j.proche.2014.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Recent Studies on Phytochemicals and Pharmacological Effects of Eleutherine Americana Merr.

Abstract: Eleutherine americana Merr., a medicinal plant, which has been widely cultivated in South East Asia. Ethnobotanically, the plant is known for treating coronary abnormality. Other pharmacological investigations showed its potency as antimicrobial and anti-inflammatory agents, and also as inhibitors ofα-glucosidase, HIV replication,and topoisomerase II. Phytochemically, three groups of compounds have been isolated i.e. naphthalene, naphtoquinone and anthraquinone. This review highlights recent data on biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
17

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 23 publications
1
47
0
17
Order By: Relevance
“…Previous research reported that there are three main groups of bioactive compounds that have been isolated from E. bulbosa; namely naphthalene, naphthoquinones, and anthraquinone (Insanu et al 2014). Liu et al (2010) and Kumar et al (2015) revealed that the dietary anthraquinone augmented weight gain and feed efficiency in the freshwater prawn species Macrobrachium rosenbergii, and also improved growth indices and total leukocyte count in fingerlings of the carp, Cirrhinus mrigala.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research reported that there are three main groups of bioactive compounds that have been isolated from E. bulbosa; namely naphthalene, naphthoquinones, and anthraquinone (Insanu et al 2014). Liu et al (2010) and Kumar et al (2015) revealed that the dietary anthraquinone augmented weight gain and feed efficiency in the freshwater prawn species Macrobrachium rosenbergii, and also improved growth indices and total leukocyte count in fingerlings of the carp, Cirrhinus mrigala.…”
Section: Discussionmentioning
confidence: 99%
“…The bulb of E. bulbosa has been known by local tribes in Kalimantan not only as a folk medicine but also as a natural antioxidant and color enhancer of meat products. The bulb is also used for enhancing breast-milk production, and to treat cardiac disease, breast cancer, stroke, hypertension, and sexual disorders (Ieyama et al 2011;Insanu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Urb. adalah tanaman herbal yang termasuk dalam famili Iridaceae [5]. Tumbuhan ini secara turun-temurun telah dipergunakan oleh masyarakat Dayak sebagai obat tradisional untuk berbagai jenis penyakit seperti kanker payudara, hipertensi, diabetes mellitus, kolesterol, jantung, dan stroke [6].…”
Section: Pendahuluanunclassified
“…Hasil ini juga sesuai dengan penelitian KLT lainnya yang berhasil mendeteksi adanya noda menggunakan eluen kloroform/ metanol (9:1 [5]. Hasil penelitian ini juga sesuai dengan penelitian aktivitas antibakteri dari ekstrak etanol kasar E. bulbosa terhadap serangkaian bakteri, termasuk S. aureus ATCC 12600.…”
unclassified
See 1 more Smart Citation